GENETIC MARKERS OF NEGATIVE OUTCOMES OF THE ACUTE CORONARY SYNDROME - N. G. Lozhkina; V. N. Maksimov; P. S. Orlov; Kuimov A. D.; M. I. Voevoda (Российский кардиологический журнал)
Aim. To evaluate the relationship of 8 mononucleotide polymorphisms (MNP) with negative longterm prognosis of the acute coronary syndrome.Material and methods. Totally 280 patients with acute coronary syndrome included (ACS), who during 1 year follow up were underwent the solid endpoints evaluation (cardiovascular death, hospitalization for recurrent ischemic event and repeated revascularization).Results. In the analysis of rs4804611 in group with negative outcomes there is significantly more prevalent genotype GG (9,1% vs. 1,8%), chances relation 5,57 (95% CI 1,35-22,96); credibility of the differences kept in men (p=0,021). In the analysis rs2549513 in the group with positive prognosis the AA genotype was more prevalent (70,6% vs. 53%), hazard ratio 0,47 (95% CI 0,26-0,85), and in the group with negative prognosis genotype AC, chances relation 2,32 (95% CI 1,28-4,20; р=0,007).While separated by gender credible differences were shown only in men (p=0,008).Conclusion. Evaluation of genetic  markers  rs4804611  and rs2549513  can significantly increase prognostic value in riskometry of ACS outcomes.